ESTETIKA MATEMATIS MOTIF SONGKET PADA ANYAMAN MENDONG TASIKMALAYA - Fitriani Muldiana; Shofa Laelatul; Neng Ani Karleni; Nani Ratnaningsih (Universitas Negeri Gorontalo, 2021)
Mathematics is an enigmatic and captivating idea. Mathematics can also be defined in the context of patterns. This is because mathematics contains patterns, structures, and depictions of an object that grows and is rooted in real life. The structure or pattern that is arranged systematically will produce work, objects, and even an agreement. Life mathematics and mathematics in school learning can be combined with aesthetic studies to achieve contextual learning. This study uses qualitative research with an ethnographic approach. The purpose of this study was to reveal the aesthetic value and mathematical concepts of the mendong woven pattern with the songket motif. The location of this research is Babakan Cikawung Village, Margabakti Village, Cibeureum Awipari District, Tasikmalaya Regency. This study involved 3 subjects. Data collection techniques were carried out through unstructured interviews, observation, documentation, and literature review. Unstructured interviews were used to ask about the craft of mendong and the process of making mending weave with songket motifs. Observations or observations are made to find mathematical concepts and mathematical aesthetic values by studying the aesthetics of Thomas Aquinas' theory. The results of the research are mathematical aesthetics by examining the theory of Thomas Aquinas. Mathematical concepts such as repeating patterns 1-2-3-4 and 4-3-2-1, geometric concepts such as parallel lines, reflection, congruence, and rhombus flat shapes.